Operational Risk Analysis Based on Enterprise Risk Management Approach (ERM) in Export Document Service Company (Case Study at CV Tarukalpa Dewata) - Ni Luh Gede Intan Diana Wahyuni; I Made Sudana; P Dyah Hudiananingsih (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
Every company in carrying out its operational activities will definitely face a risk. The various possible risks that can be experienced by the company in carrying out its operational activities need to be managed and controlled by carried out risk management. The implementation of risk management is expected to assist companies in identified, analyzed, assessed, and controlled risks and the impact of risks. One approach that can be used to perform risk management is Enterprise Risk Management (ERM). This research aims to analyze operational risks that occurred at CV Tarukalpa Dewata based on an Enterprise Risk Management (ERM) approach by identified risks, risk assessments, efforts to respond the risks and carry out risk controls to find out what actions must be taken to minimize the possibility of risks and impact risk. This research used a qualitative descriptive research method by collecting data through interviews, observations and questionnaires. The results showed that in the operational activities of CV Tarukalpa Dewata there were seventeen possible risks consisting of four risks originating from human resources owned by the company, five risks that occurred in the process of making export documents, two risks that occurred due to technological constraints, and six external risks. The results of the risk assessment showed that there were three levels of risk that occurred in the operational activities of CV Tarukalpa Dewata namely moderate, low, and very low. Responses to existing risks are carried out by monitoring, controlling management, and paying special attention (urgent) in the company's operational activities.